2018
DOI: 10.1111/1365-2435.13228
|View full text |Cite
|
Sign up to set email alerts
|

Longevity and life history coevolve with oxidative stress in birds

Abstract: The mechanisms that underpin the evolution of ageing and life histories remain elusive. Oxidative stress, which results in accumulated cellular damages, is one of the mechanisms suggested to play a role. In this paper, we set out to test the “oxidative stress theory of ageing” and the “oxidative stress hypothesis of life histories” using a comprehensive phylogenetic comparison based on an unprecedented dataset of oxidative physiology in 88 free‐living bird species. We show for the first time that bird species … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 73 publications
(218 reference statements)
4
50
0
Order By: Relevance
“…Harman () theorized further that long life spans are achieved at lower metabolic rates due to reductions in reactive oxygen species (ROS) and the damage they do to cells as a byproduct of aerobic respiration (Selman, Blount, Nussey, & Speakman, ; Speakman, ; Vágási et al, ). As a result, evolutionary ecologists and physiologists often assume negative correlations between metabolic rate and survival (Speakman et al, ), even though relationships between energy metabolism, oxidative stress and survival are complex and also affected by antioxidant defence and cellular repair pathways (Speakman, ; Vágási et al, ). Moreover, individual BMR can be highly flexible in some species and varies to accommodate seasonal changes in temperature, breeding or as part of the migratory cycle (McKechnie, ).…”
Section: Introductionmentioning
confidence: 99%
“…Harman () theorized further that long life spans are achieved at lower metabolic rates due to reductions in reactive oxygen species (ROS) and the damage they do to cells as a byproduct of aerobic respiration (Selman, Blount, Nussey, & Speakman, ; Speakman, ; Vágási et al, ). As a result, evolutionary ecologists and physiologists often assume negative correlations between metabolic rate and survival (Speakman et al, ), even though relationships between energy metabolism, oxidative stress and survival are complex and also affected by antioxidant defence and cellular repair pathways (Speakman, ; Vágási et al, ). Moreover, individual BMR can be highly flexible in some species and varies to accommodate seasonal changes in temperature, breeding or as part of the migratory cycle (McKechnie, ).…”
Section: Introductionmentioning
confidence: 99%
“…It is known that during times of stress, such as migration, birds can upregulate aspects of their antioxidant system to compensate for the increase in oxidative stressors (Cooper-Mullin and McWilliams 2016). Others have found that under physiologically challenging conditions, long-lived species have higher non-enzymatic antioxidant levels compared with shorter-lived species of birds (Vágási et al 2018), which could be a metabolic strategy in tropical bird cells to keep costs of an active antioxidant system down when there are no stressors present. Others have found that under physiologically challenging conditions, long-lived species have higher non-enzymatic antioxidant levels compared with shorter-lived species of birds (Vágási et al 2018), which could be a metabolic strategy in tropical bird cells to keep costs of an active antioxidant system down when there are no stressors present.…”
Section: Discussionmentioning
confidence: 99%
“…We propose here that, at basal levels, there are no differences in oxidative stress variables between tropical and temperate bird cell lines, however, when stressors are present, whether at the cell-level or at the whole-animal level, it may be that tropical birds have the ability to endogenously up-regulate their antioxidant system to a greater extent than temperate birds and become more resistant to cellular damage (Cohen et al 2008a, b, Jimenez et al 2013. Others have found that under physiologically challenging conditions, long-lived species have higher non-enzymatic antioxidant levels compared with shorter-lived species of birds (Vágási et al 2018), which could be a metabolic strategy in tropical bird cells to keep costs of an active antioxidant system down when there are no stressors present.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, metabolism may be decoupled from senescence because mechanisms to prevent or repair damage (e.g. endogenous antioxidants, mitochondrial membrane composition and telomere dynamics) may coevolve with metabolic rate (Brand 2000;Brand et al 2004;Monaghan & Haussmann 2006;Hulbert et al 2007;Costantini 2008;Salin et al 2015;Skrip & Mcwilliams 2016;Vagasi et al 2019;Beattie et al 2019). Furthermore, survival rates may be entirely unrelated to the accumulation of cellular damage entirely (Reznick et al 2004).…”
Section: Introductionmentioning
confidence: 99%